An exposition on complete androgen insensitivity syndrome and a case report - S. Morkos; M. Al Qasem; M. Aldam; H. K. Bhotla; A. Meyyazhagan; M. Pappuswamy; F. Iskandarani; K. Kouteich; A. Asoliman (Акушерство, гинекология и репродукция, 2025)
Complete androgen insensitivity syndrome (CAIS) is a rare X-linked sexual development condition typified by 46,XY karyotype, presence of external female genitalia along with intra-abdominal testes in labia majora or inguinal ring region. This syndrome results from alterations in the androgen receptor (AR) gene leading to primary amenorrhea and uterine agenesis (Müllerian agenesis) in adolescent teens or two-sided labial/inguinal hernia with testes in children around prepubertal age. Our paper reports a case of CAIS in a 16-year-old woman with no menarche and 46,XY karyotyping. Gonadectomy results showed hyperplasia of Leydig cells. The current research encompasses the case report and the available knowledge to date on the understanding, diagnosis, treatment, and management of CAIS.